Avaliação dos escores MELD, Child-Turcotte-Pugh, APRI, contagem de plaquetas e testes hepáticos como indicadores da presença de varizes de esôfago com ou sem necessidade de profilaxia para sangramento - Tafarel, Jean Rodrigo [UNIFESP] (2010)
Purpose: The aim of this study was to determine whether MELD, Child-Turcotte-Pugh (CTP) class, APRI and laboratory tests could predict the presence of EV or varices which need prophylactic therapy (EV with medium or large size). Methods: Three hundred cirrhotic patients (193 men; mean age 53,1 years; majority with cirrhosis from chronic C hepatitis) were prospective analyzed. Uni and multivariate analysis were used to evaluate associations between the presence of EV (any size and medium or large EV) and patients’ characteristics (MELD, CTP class, APRI, platelets count and liver tests). Small varices were regarded as those which flatten with insufflation; medium varices those which protruded less than 1/3 of the lumen and large ones those which protruded more than 1/3. Results: One hundred seventy one patients (57%) had EV, of whom 35% (105) had varices which need prophylactic therapy. The distribution of EV according to the CTP class was as follows: A, 49%; B, 75,3% and C, 80%. Independent predictors of the presence of EV were: MELD > 8 (p = 0,02); APRI > 1,64 (p = 0,01); a platelet count < 93.000/mm3 (p < 0,01); AST > 1,34xUNL (p = 0,01) and total bilirubin > 1 mg/dl (p = 0,04). MELD > 8 had the highest discriminative value for presence of EV with sensitivity of 80,1% and specificity of 51,2%. Factors independently associated with EV which need prophylactic therapy were: thrombocytopenia (< 92.000/mm3; p < 0,01) and AST > 1,47xUNL (p = 0,03). A platelet count < 92.000/mm3 had sensitivity of 65,7% and specificity of 57,9% for the presence of varices which need prophylactic therapy. Conclusions: High values on MELD are associated with EV and thrombocytopenia (< 92.000/mm3), with varices which need prophylactic therapy. Considering their low sensitivity and specificity, it is suggested to maintain the recommendation of upper gastrointestinal endoscopy for all cirrhotic patients.